Synthesis and spectral and thermal properties of copolymers of (2-cyclopentylidene-1,3-dioxolane-4-yl)methyl methacrylate with styrene and acrylonitrile and the determination of the monomer reactivity ratios - Ilter, Z; Soykan, C; Koca, M (John Wiley & Sons Inc, 2003)
The monomer (2-cyclopentylidene-1,3-dioxolane-4-yl)methyl methacrylate (CPDMMA) was synthesized by the reaction of (2-cyclopentylidene-5-hydroxymethyl-1,3-dioxolane) with methacryloyl chloride in the presence of pyridine at 0 degreesC. The radical-initiated copolymerization of CPDMMA with styrene and acrylonitrile was carried out in a 1,4-dioxane solution at 60 degreesC with 2,2'-azobisisobutyronitrile as an initiator with different monomer-to-monomer ratios in the feed. The copolymers were characterized by Fourier transform infrared and H-1 and C-13 NMR spectral studies. The copolymer composition was evaluated by the nitrogen content, and the peak integrations of H-1 NMR signals in the polymers led to the determination of the reactivity ratios. The reactivity ratios of the monomers were determined by the application of the Fineman-Ross and Kelen-Tudos linear methods and the Tidwell-Mortimer nonlinear method. The glass-transition temperatures of the two copolymer systems decreased with an increase in the molar fraction of CPDMMA in the copolymers. The thermogravimetric analysis of the copolymers revealed that the thermal stability of the two copolymer systems decreased with an increase in the molar fraction of CPDMMA in the copolymers. (C) 2003 Wiley Periodicals, Inc.
Keywords: (2-cyclopentylidene-1,3-dioxolane-4-yl)methyl methacrylate; monomer reactivity ratios; thermogravimetric analysis (TGA); glass transition; radical polymerization